Percutaneous Sclerotherapy for Management of Large Hepatic Haemangioma: First Series from Bangladesh - Moben, Ahmed Lutful; Akbar, Sheikh Mohammad Fazle; Mahtab, Musarrat; Mahmud, Tasnim; Lima, Taslima Akter; Das, Nirupoma; Nasir, Nadia Binte; Shahriar, Nasif; Abdur Rahman, Md.; Sadman, Omar Faruque; Rahim, Md. Abdur; Begum, Rokshana; et al. (British Journal of Healthcare and Medical Research, 2025)
Introduction: Hepatic haemangiomas are non-malignant hepatic vascular malformations, which are usually asymptomatic, but may be a potential cause of life-threatening complications requiring urgent surgical intervention. Methods: Of the wide range of treatment modalities currently available for hepatic haemangiomas, we opted for percutaneous sclerotherapy with a combination of bleomycin and lipiodol. Results: We included 20 patients with hepatic haemangiomas in this single arm, single centre study, all underwent percutaneous sclerotherapy with combination bleomycin and lipiodol. Patients tolerated the procedure well, with no significant adverse event reported. Reduction of size of hepatic haemangiomas was achieved in 70% of patients at 6-month follow-up. Conclusion: The study shows that percutaneous sclerotherapy with bleomycin and lipiodol is safe and effective for management of hepatic haemangiomas.